The impact of the S.A.M.R. model on the cognitive achievement of art history for students of the Institute of Fine Arts (Journal of the College of Basic Education, 2020)
The current research aims to identify:Effect of using S.A.M.R. In the collection of knowledge in modern art history.To achieve this goal, the researcher developed the following sub-objectives:1 - Design of teaching plans to teach in accordance with the model S.A.M.R in the art history of modern art.2- Measuring the effect of the teaching plans designed according to the S.A.M.R model by applying them to the students of the Institute of Fine Arts in the history of modern art.Accordingly, the researcher developed (3) zero hypotheses.The second chapter contains theoretical framework and previous studies and two topics:The first topic: the technology of education and its impact in the educational processThe second topic: Teaching models in the educational processThe third chapter, since the current research aims to know the effect of the model S.A.M.R. In the cognitive achievement of the subject of modern art history, so the researcher adopted the experimental approach in designing the research procedures because it is the most scientific methods suitable to achieve the research objectives and hypotheses.The research society consists of students of the fifth grade in the Fine Arts Department and the design department of the Fine Arts Institute for Boys - Karkh first. Therefore, the researcher conducted a survey survey aimed at identifying this community. The number of students in the fifth grade reached 109 students, (55) students in the Department of Fine Arts (drawing - sculpture - pottery - graphic) and 54 students in the design department (typography - industrial - interior - fabrics), and obtained these statistics under the letter facilitation mission issued From the Faculty of Basic Education - Mustansiriya University to the General Directorate of L First Karkh. The researcher used a set of statistical means to show the results. The research came out with a number of results, the most important of which are:The S.A.M.R. On the acquisition of knowledge information related to the material history of modern art in the students of the experimental group, which was reflected in their identification of works of art according to schools and artists who implemented them compared to their peers students control group.2. The size of the effect left by the teaching model S.A.M.R. In the experimental group (0.8). This is a good indicator of the effectiveness of this strategy in providing the students of the experimental group the educational experiences in the history of modern art compared to their peers in the control group.